Ferrite - Chen, Ruo Fei (2022)
Funding Information: Funding Stephanie Balzer: National Science Foundation Award No. CCF-1718267. Bernardo Toninho: FCT/MCTES grant NOVALINCS/BASE UIDB/04516/2020. Publisher Copyright: © Ruo Fei Chen, Stephanie Balzer, and Bernardo Toninho; licensed under Creative Commons License CC-BY 4.0